Disaster Risk Reduction Knowledge among local people in a Selected Community in the Philippines - Gil Soriano (San Beda University, 2019)
Background: The Philippines has been classified as highly vulnerable to natural disasters. Hence, reinforcing the capacities of communities towards the risk and adverse impacts of natural hazards is essential in order to reduce vulnerability and manage disasters. The study assessed disaster-related knowledge including (1) disaster preparedness and readiness, (2) disaster adaptation, (3) disaster awareness, and (4) disaster risk perception of the local people in a selected community. Methods: A descriptive-cross sectional study was utilized and a convenience sampling technique was used to select the 60 participants. The disaster risk reduction knowledge was assessed using the Disaster Risk Reduction Knowledge questionnaire. The gathered data were analyzed using frequency, percentage, mean, standard deviation and univariate linear regression. Results: The study revealed that the local people in the selected community have good knowledge on disaster preparedness and readiness, disaster adaptation, and disaster awareness and fair knowledge on disaster-related knowledge and disaster risk perception. Further, age, sex, civil status, and education did not predict the level of disaster risk reduction knowledge. Conclusion: The initiatives for disaster education in the Philippines are sufficient as evidenced by a good level of disaster risk reduction knowledge among the local people in the selected community.